Search for W and Z bosons in the reaction p̄p→twojets+γ at s=1.8TeV - Acosta, D; Affolder, T; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Ashmanskas, W; Azfar, F; et al. (2006)
We present a study of the dijet invariant mass distribution for the reaction p̄p→twojets+γ+X, at a center of mass energy of 1.8 TeV, using data collected by the CDF experiment. We compare the data to predictions for the production of a photon with two jets, together with the resonant processes p̄p→W/Z+γ+X, in which the W and Z bosons decay hadronically. A fit is made to the dijet invariant mass distribution combining the nonresonant background and resonant processes. We use the result to establish a limit for the inclusive production cross section of W/Z+γ with hadronic decay of the W and Z bosons. © 2006 The American Physical Society.